Control of Listeria monocytogenes in chicken dry-fermented sausages with bioprotective starter culture and high-pressure processing - Austrich-Comas, Anna; Serra-Castelló, Cristina; Jofré, Anna; Gou, Pere; Bover-Cid, Sara (Frontiers in Microbiology, 2022)
Listeria monocytogenes is one of the most relevant pathogens for ready-to-eat food, being a challenge for food industry to comply with microbiological criteria. The aim of the work was to assess the behaviour of L. monocytogenes in two types of chicken-based dry-fermented sausages during the fermentation and ripening, with or without a bioprotective starter culture (Latilactobacillus sakei CTC494). To complement the challenge testing approach, simulations with different predictive models were performed to better understand the role of contributing factors. The impact of post-processing strategies, such as high pressure processing and/or corrective storage was assessed. Chicken meat was inoculated with a cocktail of 3 L. monocytogenes strains, mixed with other ingredients/additives and stuffed into small (snack-type) or medium (fuet-type) casings. Snack-type was fermented (22ºC/3d) and ripened (14ºC/7d) while fuet-type was ripened (13ºC/16d). At the end of ripening, HPP (600MPa/5min) and/or corrective storage (4 or 15ºC/7d) were applied. The suitability of HPP after fermentation was evaluated in the snack-type sausages. Pathogen growth (>3 Log10) was observed only during the fermentation of the snack-type without starter. The bioprotective starter prevented the growth of L. monocytogenes in the snack-type sausages and enhanced the inactivation (1.55 Log10) in fuet-type sausages, which could be related to the higher lactic acid production and consequent decrease of pH, but also to the production of the antilisterial bacteriocin sakacin k. The gamma concept model allowed to identify the main factors controlling L. monocytogenes growth, i.e. the temperature during the early stages and aw at the end of the production process. The earlier acidification linked with the addition of starter culture made the interaction with the other factors (undissociated lactic acid, aw and temperature) be the growth preventing determinant. High pressure processing only caused a significant reduction of L. monocytogenes in snack-type, which showed higher aw. The application of HPP after fermentation did not offer a relevant advantage in terms of efficacy. Corrective storage did not promote further pathogen inactivation. The findings of the work will guide food industry to apply effective strategies (e.g. fermentation temperature and bioprotective starter cultures) to control L. monocytogenes in chicken dry-fermented sausages